Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T20:55:04+01:00
Mg + H₂SO₄ -> MgSO₄ + H₂
Mg+2H⁺+SO₄²⁻--->Mg²⁺+SO₄²⁻+H₂
Mg+2H⁺--->Mg²⁺+H₂

Mg(OH)₂ +SO₃ - > MgSO₄ + H₂O coś tu brakuuje chyba SO₃
Mg²⁺+2OH⁻ + SO₃ ---> Mg²⁺+ SO₄²⁻ + H₂O
2OH⁻+SO₃---> SO₄²⁻+H₂O

MgO + SO₃ -> MgSO₄
MgO + SO₃ --> Mg²⁺+ SO₄²⁻

Ba + 2HNO₃ - > Ba (NO₃)₂ + H₂
Ba + 2H⁺ + 2NO₃⁻---> Ba²⁺+ 2NO₃⁻+ H₂
Ba + 2H⁺---> Ba²⁺+H₂

Ba(OH)₂ + 2HNO₃ - >Ba(NO₃)₂ + 2H₂O
Ba²⁺+ 2OH⁻+ 2H⁺+ 2NO₃⁻---> Ba²⁺+ 2NO₃⁻ + H₂O
2OH⁻+ 2H⁺---> H₂O

BaCO₃ + 2HNO₃ - > Ba(NO₃)₂ + H₂0 + CO₂
Ba²⁺+ CO₃²⁻+2H⁺+ 2NO₃⁻ --->Ba²⁺+ 2NO₃⁻+ H₂0 + CO₂
CO₃²⁻+2H⁺--->H₂0 + CO₂
1 5 1